PEM electrolyzed water anode slurry and membrane electrode

By doping non-precious metal iridium-based catalysts in PEM electrolytic hydrogen production technology, combined with surfactant, the problems of high cost and low utilization rate of iridium-based catalysts are solved, and efficient and low-cost film electrode preparation is achieved.

CN120041882APending Publication Date: 2025-05-27PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311586911.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

In the existing PEM electrolytic hydrogen production technology, the high cost and low utilization rate of iridium-based catalysts are important factors that restrict large-scale development, especially in membrane electrodes, the dispersion and stability of the catalyst are difficult to take into account.

Method used

By doping non-precious metal elements into an iridium-based catalyst, an anode slurry containing iridium and non-precious metal alloys and its oxides is developed, combining anionic and cationic surfactants to improve dispersion and stability.

Benefits of technology

The high catalytic activity and stability of the iridium-based catalyst are achieved, while the mass-specific activity of the membrane electrode is improved, the loading of the iridium element is reduced, and the cost of the membrane electrode is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004571266580000131
    Figure BDA0004571266580000131
  • Figure BDA0004571266580000141
    Figure BDA0004571266580000141
Patent Text Reader

Abstract

The invention provides PEM electrolyzed water anode slurry and a membrane electrode. The anode slurry comprises an iridium-based catalyst, an anionic surfactant, a cationic surfactant, resin and a solvent, wherein the mass ratio of the sum of the mass of the anionic surfactant and the cationic surfactant to the mass of the iridium-based catalyst is (1-20): 100; the iridium-based catalyst comprises an iridium element and a non-noble metal element; the iridium-based catalyst comprises a first catalyst and a second catalyst, the first catalyst comprises elemental iridium and / or an alloy of iridium and a non-noble metal, and the second catalyst comprises an oxide of iridium and / or an oxide of the alloy of iridium and the non-noble metal. The invention also provides a membrane electrode containing the anode slurry or prepared from the anode slurry. The iridium-based catalyst of the anode slurry has high catalytic activity and high catalytic stability, and also has relatively high suspension stability, so that the mass ratio activity of a membrane electrode can be improved, the loading capacity of elemental iridium is reduced, and the cost of the membrane electrode is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production by electrolyzing water, and particularly relates to a PEM electrolyzed water anode paste and a membrane electrode. Background Art

[0002] The proton exchange membrane (PEM) electrolyzed water hydrogen production technology based on renewable energy is one of the effective methods for large-scale production of green hydrogen in the future. It has the advantages of high working efficiency, high hydrogen production purity, compact electrolyzer and system structure, high inherent safety, large adjustable range of load fluctuation, and suitability for rapid start and stop. The anodic reaction is the rate-determining step, and the activity, efficiency and cost of the anode catalyst are one of the important factors restricting the large-scale development of PEM electrolyzed water hydrogen production at present. The current main commercial anode catalyst is IrO 2 or Ir black catalyst. The reserves of Ir are scarce and the price is expensive. Therefore, the urgent task is to develop an efficient preparation method of membrane electrode paste to reduce the amount of iridium-based catalyst, improve the utilization rate of iridium-based catalyst, and reduce the amount of iridium catalyst to reduce the cost.

[0003] As the core component of PEM electrolyzed water, the membrane electrode is not only an important place for electron generation and separation, but also plays a role in transporting water and discharging gas. The membrane electrode mainly consists of a proton exchange membrane, a catalytic layer and a diffusion layer. The microscopic structure of the catalytic layer in the membrane electrode is determined by the paste coated on the proton exchange membrane, and the composition and dispersion degree of the paste have a great influence on the catalyst active area, the migration speed of protons and electrons. The preparation of the catalyst paste is crucial, and its performance will directly affect the catalytic performance of the prepared membrane electrode and ultimately affect the performance of PEM electrolyzed water.

[0004] During the preparation process of the membrane electrode catalyst paste, the biggest problem is the dispersibility and suspension stability of the paste. Adding a high-polymer proton conductor solution or a surfactant can prevent the agglomeration and sedimentation of the iridium-based catalyst and improve the dispersibility of the paste. Commonly used high-polymer proton conductor solutions are long-side-chain perfluorosulfonic acid resins (such as Nafion resin, DuPont) and short-side-chain perfluorosulfonic acid resins (such as Aquivion resin, Solvay). When preparing the catalyst paste with different types of perfluorosulfonic acid resins, the membrane electrode will exhibit different catalytic characteristics. In addition to the type of resin, other factors such as the ratio and existence form of other components in the paste will also have a great impact on the catalytic performance of the membrane electrode. Therefore, the preparation method of the catalyst paste is the key to improving its catalytic performance.

[0005] The existence form of the iridium-based catalyst is the main factor affecting the oxygen evolution performance of the iridium oxide catalyst. The iridium-based catalysts applied industrially can generally be divided into Ir black, IrO2 and IrOx catalysts. The IrOx bulk structure is rich in oxygen defects and contains a large number of hydroxyl groups on the surface. In terms of oxygen evolution performance, the stability of Ir black is not as good as that of IrO2 and IrOx, but it has better activity than IrO2 and IrOx catalysts. The difference in this activity and stability stems from the different oxygen evolution mechanisms of the two catalysts. To reduce the amount of Ir used and improve the activity and efficiency of the catalyst, researchers have developed doped non-noble metal iridium-based catalysts to increase the utilization rate of Ir, improve the performance of the catalyst, and thereby reduce the cost of the catalyst. Pure iridium-based elemental or iridium-based oxidized catalysts are difficult to simultaneously achieve both activity and stability. Therefore, the utilization rate of iridium-based catalysts is improved through the synergistic effect of at least two iridium-based catalysts with different valence states. However, when preparing a slurry with both iridium-based elemental and iridium-based oxidized catalysts, there is a disadvantage of poor suspension stability. Since Ir resources are scarce and expensive, improving the utilization rate of iridium-based catalysts is of utmost importance. Given the important application value of iridium-based nanomaterials in PEM electrolysis water technology, to achieve the large-scale popularization and application of PEM electrolysis water technology, there is an urgent need to develop a preparation method for highly efficient and low-cost iridium-based catalyst membrane electrode slurry. Summary of the Invention

[0006] To solve the above problems, the object of the present invention is to provide a PEM electrolysis water anode slurry and a membrane electrode. The iridium-based catalyst of this anode slurry can still have both high catalytic activity and high catalytic stability when doped with non-noble metals, and at the same time has high suspension stability, which can improve the mass-specific activity of the membrane electrode, reduce the loading of iridium elemental, and thereby reduce the cost of the membrane electrode.

[0007] To achieve the above object, the present invention provides a PEM electrolysis water anode slurry, which includes: an iridium-based catalyst, an anionic surfactant, a cationic surfactant, a resin, and a solvent; wherein, the mass ratio of the sum of the masses of the anionic surfactant and the cationic surfactant to the mass of the iridium-based catalyst is 1-20:100; the iridium-based catalyst contains iridium element and non-noble metal elements; the iridium-based catalyst includes a first catalyst and a second catalyst, the first catalyst includes iridium elemental and / or an alloy of iridium and non-noble metals, and the second catalyst includes an oxide of iridium and / or an oxide of an alloy of iridium and non-noble metals.

[0008] The present invention has found through research that by doping non-noble metals in the iridium-based catalyst, the amount of Ir used can be reduced while at least maintaining the activity and efficiency of the catalyst; in some specific embodiments, doping non-noble metals can also improve the utilization rate of Ir in the iridium-based catalyst, improve the activity and efficiency of the catalyst, and thereby reduce the cost while improving the performance of the catalyst.

[0009] In the above anode slurry, the alloy of iridium and non-noble metals is denoted as Ir x M 1-x and the oxide of the alloy of iridium and non-noble metals is denoted as Ir x M 1-x Oy where M is a non-noble metal. In the alloy of iridium and non-noble metal and the oxide of the alloy of iridium and non-noble metal, the non-noble metal element may include Co, that is, element M includes Co. Specifically, the alloy of iridium and non-noble metal may include an iridium-cobalt alloy; the oxide of the alloy of iridium and non-noble metal includes the oxide of the iridium-cobalt alloy.

[0010] In the above-mentioned anode paste, the composition of the iridium-based catalyst may include:

[0011] Combination (1): elemental iridium, oxide of iridium-cobalt alloy;

[0012] Combination (2): elemental iridium, iridium-cobalt alloy, oxide of iridium;

[0013] Combination (3): elemental iridium, oxide of iridium, oxide of iridium-cobalt alloy;

[0014] Combination (4): iridium-cobalt alloy, oxide of iridium;

[0015] Combination (5): iridium-cobalt alloy, oxide of iridium-cobalt alloy;

[0016] Combination (6): iridium-cobalt alloy, oxide of iridium, oxide of iridium-cobalt alloy;

[0017] Combination (7): elemental iridium, iridium-cobalt alloy, oxide of iridium, oxide of iridium-cobalt alloy.

[0018] In the above-mentioned anode paste, the iridium element in the first catalyst is in the elemental state and has high hydrogen evolution activity; the second catalyst is in the oxide state and has high stability. By adding both the alloy and the oxide of the alloy as catalysts in the anode paste of the present invention, the first catalyst and the second catalyst cooperate with each other, enabling the iridium-based catalyst to have both high activity and high stability.

[0019] In the above-mentioned anode paste, the mass ratio of the first catalyst to the second catalyst is 1:1 - 10, and specifically, it can be specific values such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., and ranges with any two of the above specific values as endpoints.

[0020] In the above-mentioned anode paste, when the first catalyst includes elemental iridium and an alloy of iridium and non-noble metal, the mass ratio of the elemental iridium to the alloy of iridium and non-noble metal is greater than or equal to 1:1.

[0021] In the above-mentioned anode paste, when the second catalyst includes the oxide of iridium and the oxide of the alloy of iridium and non-noble metal, the mass ratio of the oxide of iridium to the oxide of the alloy of iridium and non-noble metal is greater than or equal to 1:1.

[0022] In the above-mentioned anode paste, in the alloy of iridium and non-noble metals, by element, the mass ratio of iridium to non-noble metals is greater than or equal to 6:4; that is, the mass percentage content of iridium element in the alloy of iridium and non-noble metals is generally greater than 60% and less than 100%. Specifically, the mass ratio of iridium to non-noble metals can be specific values such as 6:4, 7:3, 8:2, 9:1, etc., and ranges with any two of the above specific values as endpoints.

[0023] In the above-mentioned anode paste, in the oxide of the alloy of iridium and non-noble metals, by element, the mass ratio of iridium to non-noble metals is greater than or equal to 6:4. Specifically, the mass ratio of iridium to non-noble metals can be specific values such as 6:4, 7:3, 8:2, 9:1, etc., and ranges with any two of the above specific values as endpoints.

[0024] In the anode paste of the present invention, the mass ratio of iridium to non-noble metals in the alloy of iridium and non-noble metals and the mass ratio in the oxide of the alloy of iridium and non-noble metals can be the same or different.

[0025] In the above-mentioned anode paste, the oxide of iridium generally has oxygen vacancies, denoted as IrOx. There are oxygen defects in the bulk structure of this oxide and a large number of hydroxyl groups on the surface. Based on the mass of the oxide of iridium being 100%, the mass of oxygen element in the oxide of iridium can be controlled to be below 30%, specifically it can be specific values such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., and ranges with any two of the above specific values as endpoints. In some specific implementation schemes, the mass content of oxygen element in the oxide of iridium can be 10%-30%, 20%-30%, etc.

[0026] In the above-mentioned anode paste, the oxide of the alloy of iridium and non-noble metals generally has oxygen vacancies, denoted as Ir x M 1-x O y .. There are oxygen defects in the bulk structure of this oxide and a large number of hydroxyl groups on the surface. Based on the mass of the oxide of the alloy of iridium and non-noble metals being 100%, the mass content of oxygen element in the oxide of the alloy of iridium and non-noble metals can be controlled to be below 30%, specifically it can be specific values such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., and ranges with any two of the above specific values as endpoints. In some specific implementation schemes, the mass content of oxygen element in the oxide of the alloy of iridium and non-noble metals can be 10%-30%, 20%-30%, etc.

[0027] In the above-mentioned anode paste, the mass ratio of the iridium-based catalyst in the anode paste is 1%-4%, specifically, it can be specific values such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc., and ranges with any two of the above specific values as endpoints.

[0028] In the above-mentioned anode paste, the iridium element specifically may include iridium black.

[0029] In the present invention, the preparation method of the above-mentioned iridium black may include: mixing an inorganic salt of iridium with a reducing agent, reacting to obtain iridium black. In some specific embodiments, the inorganic salt of iridium may include a chloride salt of iridium, such as iridium trichloride, and the reducing agent may include a strong reducing agent, such as sodium borohydride. The reaction temperature may be 120°C, and the reaction time may be 6 h.

[0030] In some specific embodiments, the preparation method of the above-mentioned iridium black may include: mixing an alcohol solution of iridium trichloride (the solvent may be an alcohol, such as ethylene glycol, etc.) with a solution of sodium borohydride (the solvent may be water), stirring and reacting at 120°C for 6 h, evaporating, grinding, washing 3 times (it may be water washing), and drying to obtain iridium black.

[0031] In the above-mentioned anode paste, the iridium oxide can be formed by calcining the iridium element. Specifically, the calcination process may include a first calcination and a second calcination carried out in sequence. The iridium element may be iridium black.

[0032] In the above-mentioned calcination process, the temperature of the first calcination may be 120-180°C, specifically, it can be specific values such as 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc., and ranges with any two of the above specific values as endpoints; the time of the first calcination is 1-2 h, specifically, it can be specific values such as 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2 h, etc., and ranges with any two of the above specific values as endpoints.

[0033] In the above-mentioned calcination process, the temperature of the second calcination is 300-400°C, specifically, it can be specific values such as 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, etc., and ranges with any two of the above specific values as endpoints; the time of the second calcination is 2-4 h, for example, it can be specific values such as 2 h, 2.5 h, 3 h, 3.5 h, 4 h, etc., and ranges with any two of the above specific values as endpoints.

[0034] In some specific embodiments, the method for preparing the iridium oxide may specifically include: placing iridium in a tube furnace, calcining at 150 °C for 1 h, and then calcining at 350 °C for 3 h to obtain the iridium oxide.

[0035] In the above anodic paste, the method for preparing the alloy of iridium and non-noble metal includes: mixing an inorganic salt of iridium, a salt of non-noble metal, a ligand, and a reducing agent, reacting in a closed environment, and cooling to obtain the alloy of iridium and non-noble metal.

[0036] In some specific embodiments, the ligand may include citric acid, etc. The salt of non-noble metal may be an acetylacetonate salt. The reaction temperature may be 120 °C, and the reaction time may be 6 h.

[0037] In some specific embodiments, the method for preparing the alloy of iridium and non-noble metal may specifically include: mixing an inorganic salt of iridium, a salt of non-noble metal, a ligand, and a reducing agent to form a reaction solution (ultrasonic assistance for dispersion can be used, and the ultrasonic time can be 1 h); transferring the reaction system to a high-pressure reaction kettle, reacting at 120 °C for 3 h, cooling, forming a nano-alloy cluster of iridium and non-noble metal after cooling, washing 3 times (it can be washed with ethanol), and drying to obtain the alloy of iridium and non-noble metal.

[0038] In the above method for preparing the alloy of iridium and non-noble metal, the reducing agent may include benzyl alcohol. The reaction in the above preparation process is carried out in a closed environment at 120 °C (for example, it can be a high-pressure reaction kettle), and the reaction is in a high-pressure environment. At this time, benzyl alcohol has reducibility and can reduce metal salts (such as inorganic salts of iridium and salts of non-noble metals).

[0039] In some specific embodiments, the oxide of the alloy of iridium and non-noble metal can be formed by calcining the alloy of iridium and non-noble metal.

[0040] In the above calcination process, the temperature of the first calcination can be 120 - 180 °C, specifically, it can be specific values such as 120 °C, 130 °C, 140 °C, 150 °C, 160 °C, 170 °C, 180 °C, etc., and ranges with any two of the above specific values as endpoints; the time of the first calcination is 1 - 2 h, specifically, it can be specific values such as 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2 h, etc., and ranges with any two of the above specific values as endpoints.

[0041] In the above calcination process, the temperature of the second calcination is 300 - 400 °C, specifically it can be specific values such as 300 °C, 310 °C, 320 °C, 330 °C, 340 °C, 350 °C, 360 °C, 370 °C, 380 °C, 390 °C, 400 °C, etc. and ranges with any two of the above specific values as endpoints; the time of the second calcination is 2 - 4 h, for example, specific values such as 2 h, 2.5 h, 3 h, 3.5 h, 4 h, etc. and ranges with any two of the above specific values as endpoints.

[0042] In some specific embodiments, the method for preparing the oxide of the iridium and non - precious metal alloy may include: calcining the alloy of iridium and non - precious metal at 120 - 180 °C for 1 - 2 h, and then calcining at 300 - 400 °C for 2 - 4 h to obtain the oxide of the iridium and non - precious metal alloy.

[0043] In the anode paste, due to the different densities of the alloy catalyst and the oxide catalyst of the alloy, it is very difficult to uniformly disperse them in the same system, and both the alloy and the oxide of the alloy are not charged and are prone to aggregation. In this regard, the present invention can form vesicles in the anode paste by adding an anionic surfactant and a cationic surfactant. These vesicles can effectively encapsulate the catalyst particles (alloy particles and oxide particles of the alloy), making the particles uniformly dispersed, preventing particle agglomeration, facilitating the formation of a suspension and improving the dispersibility and suspension stability of the paste.

[0044] In the above anode paste, the mass ratio of the sum of the masses of the anionic surfactant and the cationic surfactant to the mass of the iridium - based catalyst is generally 1 - 20:100. The above mass ratio can specifically be specific values such as 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 15:100, 20:100, etc. and ranges with any two of the above specific values as endpoints. In some specific embodiments, the above mass ratio can be 3 - 9:100.

[0045] In the above anode paste, the mass ratio of the anionic surfactant to the cationic surfactant can be controlled to be 2 - 5:1, for example, specific values such as 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc. and ranges with any two of the above specific values as endpoints. In some specific embodiments, the mass ratio of the anionic surfactant to the cationic surfactant can be controlled to be 2 - 4:1.

[0046] In the above-mentioned anode paste, the sum of the mass percentages of the anionic surfactant and the cationic surfactant in the anode paste is 0.03% - 0.2%, specifically, it can be specific values such as 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, etc., and ranges with any two of the above specific values as endpoints.

[0047] In the above-mentioned anode paste, the anionic surfactant is generally an anionic surfactant with a hydrophilic group, and specifically, it can include one or a combination of two or more of alkylbenzene sulfonic acid surfactants, perfluoroalkyl sulfonic acid surfactants, perfluoroalkyl sulfuric acid surfactants, alkylbenzene sulfuric acid surfactants, perfluoroalkyl carboxylic acid surfactants, alkylbenzene carboxylic acid surfactants, perfluoroalkyl phosphoric acid surfactants, and alkylbenzene phosphoric acid surfactants. In some specific embodiments, the anionic surfactant can include perfluoroalkyl carboxylic acid and / or alkylbenzene sulfonic acid.

[0048] In some specific embodiments, the carbon number of the anionic surfactant can be 12 - 18, specifically, it can be specific values such as 12, 13, 14, 15, 16, 17, 18, etc., and ranges with any two of the above specific values as endpoints.

[0049] In the above-mentioned anode paste, the cationic surfactant includes one or a combination of two or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride, dodecyldimethylbenzylammonium chloride, and octadecyltrimethylammonium chloride. In some specific embodiments, the cationic surfactant can include cetyltrimethylammonium bromide.

[0050] In the above-mentioned anode paste, the mass ratio of the resin to the iridium-based catalyst is 1:3 - 8, specifically, it can be specific values such as 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, etc., and ranges with any two of the above specific values as endpoints.

[0051] In the above-mentioned anode paste, the resin can be added in the form of a resin solution. The mass concentration of this resin solution can be controlled to be 1% - 5%, for example, it can be specific values such as 1%, 2%, 3%, 4%, 5%, etc., and ranges with any two of the above specific values as endpoints.

[0052] In the above-mentioned anode paste, the solvent includes water and alcohol, and the alcohol includes one or a combination of two or more of ethylene glycol, glycerol, ethanol, and propanol. In some specific embodiments, isopropyl alcohol can be used as the alcohol.

[0053] In the above anode slurry, the mass ratio of alcohol to water in the solvent may be 3-8:1.

[0054] The present invention also provides a method for preparing the above-mentioned PEM water electrolysis anode slurry, comprising:

[0055] An iridium-based catalyst, an anionic surfactant, a cationic surfactant, a resin and a solvent are mixed to form a raw material mixture, and the raw material mixture is ultrasonically vibrated and ball-milled to obtain the anode slurry.

[0056] In the above-mentioned method for preparing the anode slurry, the power of the ultrasound can be controlled to be 350-750W, for example, 500W; the time of the ultrasound can be controlled to be 10min-30min.

[0057] In the above-mentioned method for preparing the anode slurry, the rotation speed of the ball mill can be controlled to be 300-500 rpm, such as 400 rpm; the time of the ball milling can be controlled to be 60-180 min, such as 120 min. The particle size of the particles in the anode slurry after ball milling is 2nm-5nm.

[0058] The present invention also provides a membrane electrode, which is made of the above-mentioned PEM water electrolysis anode slurry or contains the above-mentioned PEM water electrolysis anode slurry. In some specific embodiments, the above-mentioned PEM water electrolysis anode slurry provided by the present invention can be used as an anode catalyst layer, and is assembled with the cathode catalyst layer to the opposite sides of the proton exchange membrane to form a membrane electrode. The above-mentioned PEM water electrolysis anode slurry provided by the present invention has high suspension stability, and the mass specific activity of the membrane electrode made therefrom is improved, which can reduce the loading of iridium single substance and reduce costs.

[0059] The beneficial effects of the present invention include:

[0060] 1. The PEM water electrolysis anode slurry provided by the present invention can take into account the characteristics of high catalytic activity and high catalytic stability of the two catalysts by introducing iridium-based alloys and iridium-based alloy oxides in a single substance state as catalysts. The mass specific activity of the membrane electrode made of the anode slurry is improved. By doping some non-precious metals, the iridium loading can be reduced while reducing the catalytic activity and stability, thereby reducing the cost of the membrane electrode.

[0061] 2. The PEM water electrolysis anode slurry provided by the present invention can improve the dispersibility of the iridium-based catalyst and avoid particle agglomeration by introducing anionic surfactants and cationic surfactants, thereby improving the suspension stability of the anode slurry. DETAILED DESCRIPTION

[0062] For a clearer understanding of the technical features, objectives, and beneficial effects of the present invention, the following detailed description of the technical solution of the present invention is provided, but it should not be construed as a limitation on the scope of implementation of the present invention.

[0063] The preparation method of the iridium black catalyst used in the following examples and comparative examples is as follows:

[0064] Dissolve 1 g of iridium trichloride in 100 mL of ethylene glycol, and stir well to form solution a. Dissolve 47.5 mg of sodium borohydride in 10 mL of distilled water to form solution b. Drop solution b into solution a, heat and stir at 120 °C for 6 h, and slowly evaporate the solution to dryness. After grinding the dried solid sample, wash it 3 times repeatedly with pure water and dry it overnight. The obtained powder sample, Ir black, is the Ir black catalyst.

[0065] The preparation method of the IrOx catalyst used in the following examples and comparative examples is as follows:

[0066] Place the above-prepared powder sample Ir black in a tubular furnace, calcine it at 150 °C for 1 h and at 350 °C for 3 h. After cooling to room temperature, grind the product thoroughly to obtain the powder sample IrO x , which is the IrO x catalyst. The mass percentage of oxygen element in this catalyst is 12%.

[0067] The preparation method of the Ir x C o1-x alloy catalyst used in the following examples and comparative examples is as follows:

[0068] Weigh 10 mg of iridium trichloride, 12 mg of cobalt acetylacetonate, and 100 mg of citric acid into a 50 ml flask, add 20 ml of benzyl alcohol, and ultrasonically disperse for about 1 h. Transfer the mixed solution to a high-pressure reaction kettle and place it in a rotary oven. React at 120 °C with rotation for 3 h. After the reaction naturally cools to room temperature, IrCo alloy nanoclusters are obtained. Wash the obtained product 3 times with ethanol to obtain the Ir x C o1-x catalyst (x = 0.42), and dry it for standby.

[0069] The preparation method of the Ir x Co 1-x O y alloy catalyst used in the following examples and comparative examples is as follows:

[0070] Place the Ir x Co 1-x alloy catalyst powder sample prepared above in a tubular furnace, calcine it at 150 °C for 1 h and at 330 °C for 3 h. After cooling to room temperature, grind the product thoroughly to obtain the powder sample Ir x Co1-x O y The mass percentage of oxygen element in this catalyst is 15%. The molar ratio of iridium to cobalt in this sample is the same as that of Ir x Co 1-x and x = 0.42.

[0071] Example 1

[0072] This example provides a PEM electrolytic water anode paste, and the preparation method of this anode paste includes:

[0073] Weigh 4 mg of Ir black catalyst, 8 mg of Ir x catalyst, 8 mg of Ir x Co 1-x O y catalyst, slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid, and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, continue to ultrasonically vibrate for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically vibrated for another 30 min, place it in the ultrasonic for standby use, and thus obtain the anode catalyst paste S1.

[0074] Example 2

[0075] This example provides a PEM electrolytic water anode paste, and the preparation method of this anode paste includes:

[0076] Weigh 2 mg of Ir black catalyst, 2 mg of Ir x Co 1-x alloy catalyst, 16 mg of Ir x Co 1-x O y catalyst, slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid, and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, continue to ultrasonically vibrate for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically vibrated for another 30 min, place it in the ultrasonic for standby use, and thus obtain the anode catalyst paste S2.

[0077] Example 3

[0078] This embodiment provides a PEM electrolyzed water anode slurry, and the preparation method of the anode slurry includes:

[0079] Weigh 4 mg of Ir black catalyst and 16 mg of Ir x Co 1-x O y catalyst. Slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then sequentially add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture to form a raw material mixture, and continue ultrasonication for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically vibrated for another 30 min, place it in the ultrasonic for standby, and thus obtain the anode catalyst slurry S3.

[0080] Example 4

[0081] This embodiment provides a PEM electrolyzed water anode slurry, and the preparation method of the anode slurry includes:

[0082] Weigh 4 mg of sample Ir x Co 1-x alloy catalyst and 16 mg of IrO x catalyst. Slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then sequentially add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture to form a raw material mixture, and continue ultrasonication for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically vibrated for another 30 min, place it in the ultrasonic for standby, and thus obtain the anode catalyst slurry S4.

[0083] Example 5

[0084] This embodiment provides a PEM electrolyzed water anode slurry, and the preparation method of the anode slurry includes:

[0085] Weigh 4 mg of Ir black catalyst, 8 mg of IrO x catalyst and 8 mg of Ir x Co 1-x O y8 mg of catalyst, 200 mg of water was slowly added thereto, 1.2 mg of dodecylbenzenesulfonic acid and 0.6 mg of cetyltrimethylammonium bromide were added to form a mixed solution, and the mixed solution was ultrasonically vibrated (ultrasonic power was 500 W) for 10 min. Then, 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) were successively added to the above mixture to form a raw material mixture, and ultrasonic treatment was continued for 20 min to make it uniformly mixed. Ball milling was carried out for 30 min (rotation speed was 350 rpm) using a ball mill. After the mixed solution was ultrasonically treated for another 30 min, it was placed in the ultrasonic device for standby use, and thus the anode catalyst slurry S5 was obtained.

[0086] Example 6

[0087] This example provides a PEM electrolyzed water anode slurry, and the preparation method of the anode slurry includes:

[0088] Weigh 4 mg of Ir black catalyst, IrO x 8 mg of catalyst, Ir x Co 1-x O y 8 mg of catalyst, 200 mg of water was slowly added thereto, 1.2 mg of dodecylbenzenesulfonic acid and 0.3 mg of cetyltrimethylammonium bromide were added to form a mixed solution, and the mixed solution was ultrasonically vibrated (ultrasonic power was 500 W) for 10 min. Then, 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) were successively added to the above mixture to form a raw material mixture, and ultrasonic treatment was continued for 20 min to make it uniformly mixed. Ball milling was carried out for 30 min (rotation speed was 350 rpm) using a ball mill. After the mixed solution was ultrasonically treated for another 30 min, it was placed in the ultrasonic device for standby use, and thus the anode catalyst slurry S6 was obtained.

[0089] Example 7

[0090] This example provides a PEM electrolyzed water anode slurry, and the preparation method of the anode slurry includes:

[0091] Weigh 3 mg of Ir black catalyst, Ir x Co 1-x 1 mg of alloy catalyst, Ir x Co 1-x O yWeigh 16 mg of the catalyst, slowly add 200 mg of water to it, add 0.4 mg of dodecylbenzenesulfonic acid and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic bath for standby, and thus obtain the anode catalyst slurry S7.

[0092] Example 8

[0093] This example provides a PEM electrolytic water anode slurry, and the preparation method of this anode slurry includes:

[0094] Weigh 4 mg of Ir black catalyst, Ir x Co 1-x O y Weigh 16 mg of the catalyst, slowly add 200 mg of water to it, add 0.6 mg of dodecylbenzenesulfonic acid and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic bath for standby, and thus obtain the anode catalyst slurry S8.

[0095] Comparative Example 1

[0096] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of this anode slurry includes:

[0097] Weigh 20 mg of Ir black catalyst, slowly add 200 mg of water to it, add 0.4 mg of dodecylbenzenesulfonic acid and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution, and ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic bath for standby, and thus obtain the anode catalyst slurry C1.

[0098] Comparative Example 2

[0099] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0100] Weigh 20 mg of IrO x catalyst, slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid, and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution. Ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic device for standby, and thus obtain the anode catalyst slurry C2.

[0101] Comparative Example 3

[0102] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0103] Weigh 4 mg of Ir black catalyst and 16 mg of Ir x Co 1-x alloy catalyst, slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid, and 0.2 mg of cetyltrimethylammonium bromide to form a mixed solution. Ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic device for standby, and thus obtain the anode catalyst slurry C3.

[0104] Comparative Example 4

[0105] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0106] Weigh 4 mg of IrO x catalyst, Ir x Co 1-x O y16 mg of catalyst, 200 mg of water was slowly added thereto, 0.4 mg of dodecylbenzenesulfonic acid and 0.2 mg of cetyltrimethylammonium bromide were added to form a mixed solution, and the mixed solution was ultrasonically vibrated (ultrasonic power was 500 W) for 10 min. Then 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) were successively added to the above mixture to form a raw material mixture, and ultrasonication was continued for 20 min to make it uniformly mixed. Ball milling was carried out for 30 min (rotation speed was 350 rpm) using a ball mill. After the mixed solution was ultrasonically treated for 30 min, it was placed in the ultrasonic for standby use, and the anode catalyst slurry C4 was obtained.

[0107] Comparative Example 5

[0108] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0109] Weigh 4 mg of Ir black catalyst, IrO x catalyst 8 mg, Ir x Co 1-x O y catalyst 8 mg, 200 mg of water was slowly added thereto, 0.4 mg of dodecylbenzenesulfonic acid was added to form a mixed solution, and the mixed solution was ultrasonically vibrated (ultrasonic power was 500 W) for 10 min. Then 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) were successively added to the above mixture to form a raw material mixture, and ultrasonication was continued for 20 min to make it uniformly mixed. Ball milling was carried out for 30 min (rotation speed was 350 rpm) using a ball mill. After the mixed solution was ultrasonically treated for 30 min, it was placed in the ultrasonic for standby use, and the anode catalyst slurry C5 was obtained.

[0110] Comparative Example 6

[0111] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0112] Weigh 4 mg of Ir black catalyst, IrO x catalyst 8 mg, Ir x Co 1-x O y catalyst 8 mg, 200 mg of water was slowly added thereto, 2 mg of dodecylbenzenesulfonic acid and 1 mg of cetyltrimethylammonium bromide were added to form a mixed solution, and the mixed solution was ultrasonically vibrated (ultrasonic power was 500 W) for 10 min. Then 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) were successively added to the above mixture to form a raw material mixture, and ultrasonication was continued for 20 min to make it uniformly mixed. Ball milling was carried out for 30 min (rotation speed was 350 rpm) using a ball mill. After the mixed solution was ultrasonically treated for 30 min, it was placed in the ultrasonic for standby use, and the anode catalyst slurry C6 was obtained.

[0113] Comparative Example 7

[0114] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0115] Weigh 4 mg of Ir black catalyst, IrO x catalyst 8 mg, Ir x Co 1-x O y catalyst 8 mg, slowly add 200 mg of water thereto, add 0.2 mg of dodecylbenzenesulfonic acid, and 0.1 mg of cetyltrimethylammonium bromide to form a mixed solution. Ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic device for standby, and thus obtain the anode catalyst slurry C7.

[0116] Comparative Example 8

[0117] This comparative example provides a PEM electrolytic water anode slurry, and the preparation method of the anode slurry includes:

[0118] Weigh 4 mg of Ir black catalyst, IrO x catalyst 8 mg, Ir x Co 1-x O y catalyst 8 mg, slowly add 200 mg of water thereto, add 0.4 mg of dodecylbenzenesulfonic acid, and 0.4 mg of cetyltrimethylammonium bromide to form a mixed solution. Ultrasonically vibrate the mixed solution (ultrasonic power is 500 W) for 10 min. Then, add 700 mg of isopropanol and 80 mg of Nafion resin solution (5 wt%) to the above mixture in sequence to form a raw material mixture, and continue ultrasonic treatment for 20 min to make it evenly mixed. Ball mill for 30 min (rotation speed is 350 rpm). After the mixed solution is ultrasonically treated for another 30 min, place it in the ultrasonic device for standby, and thus obtain the anode catalyst slurry C8.

[0119] Test Example

[0120] This test example provides the performance test results of the anode slurries prepared in the above examples and comparative examples. The test process is as follows:

[0121] The anodic catalyst layers of the CCMs were respectively prepared from the anodic slurries prepared in Examples 1 to 4 and Comparative Examples 1 to 4. The proton exchange membrane was a Nafion 115 membrane, and the cathodic catalyst layer was Pt / C. The iridium-based catalyst loading in the anode prepared was 0.42 mg / cm 2 , and the Pt loading in the cathode was 0.25 mg / cm 2 . The anodic catalyst layer, cathodic catalyst layer, and proton exchange membrane were assembled into a single cell (i.e., a membrane electrode) for water electrolysis performance testing. The test conditions were standard atmospheric pressure and a temperature of 50 °C. The electrolysis voltage at 2 A / cm 2 was tested.

[0122] Table 1

[0123]

[0124]

[0125] The water electrolysis test results are shown in Table 1. It can be seen from Table 1 that the membrane electrode voltages of Examples 1 to 4 are much lower than those of Comparative Examples 1 to 4. This result shows that adding both elemental iridium-based catalyst and oxidized iridium-based catalyst in the anodic slurry can endow the catalyst in the slurry with high hydrogen evolution activity and catalytic stability, and can improve the mass specific activity and suspension stability of the anodic slurry.

[0126] Specifically, by comparing Comparative Examples 1 to 4 with each example, it can be seen that, compared with the single-component catalyst, the present invention can improve the hydrogen evolution activity and catalytic stability of the catalyst by adding both elemental and oxidized catalysts in the iridium-based catalyst, and thus reduce the electrolysis voltage of the membrane electrode made of the anodic slurry.

[0127] By comparing Comparative Example 5 with each example, it can be seen that, compared with adding only one ionic surfactant, the present invention can improve the stability of the anodic slurry and reduce the electrolysis voltage of the membrane electrode by adding two ionic surfactants with opposite electric charges in the anodic slurry.

[0128] By comparing Comparative Examples 6 to 8, it can be seen that by controlling the concentrations of the two surfactants in the anodic slurry and the ratio between the two surfactants, it is helpful to improve the dispersibility of the catalyst particles in the slurry, thereby enhancing the suspension stability of the slurry.

[0129] The above test results show that by adding both a cationic surfactant and an anionic surfactant to the anode paste in the present invention, the two surfactants can produce a synergistic effect, thereby preventing agglomeration between catalyst particles (iridium metal, iridium oxide, alloy of iridium and non-noble metal, oxide of alloy of iridium and non-noble metal), effectively improving the dispersibility and suspension stability of the anode paste. This anode paste has both the high catalytic activity of iridium metal and the high catalytic stability of oxide, can improve the mass specific activity of the membrane electrode, and can reduce the loading of iridium metal and the cost of the membrane electrode.

Claims

1. A PEM water electrolysis anode slurry, the anode slurry include: Iridium-based catalysts, anionic surfactants, cationic surfactants, resins, solvents; Wherein, the mass ratio of the sum of the mass of the anionic surfactant and the cationic surfactant to the mass of the iridium-based catalyst is 1-20:100; The iridium-based catalyst comprises iridium element and non-precious metal element; The iridium-based catalyst includes a first catalyst and a second catalyst, wherein the first catalyst includes iridium simple substance and / or an alloy of iridium and a non-precious metal, and the second catalyst includes iridium oxide and / or an oxide of an alloy of iridium and a non-precious metal.

2. The anode slurry according to claim 1, in, The non-precious metal includes cobalt.

3. The anode slurry according to claim 1 or 2, in, In the alloy of iridium and non-precious metal, the mass ratio of iridium to non-precious metal is greater than or equal to 6:4, calculated on an element basis.

4. The anode slurry according to claim 1 or 2, in, In the oxide of the iridium and non-precious metal alloy, the mass ratio of the iridium to the non-precious metal, calculated as the element, is greater than or equal to 6:4; The mass of oxygen element in the oxide of iridium and non-noble metal alloy is 30% or less, based on 100% by mass of the oxide of iridium and non-noble metal alloy.

5. The anode slurry according to claim 1, in, The mass of oxygen element in the iridium oxide is 30% or less, based on 100% of the mass of the iridium oxide.

6. The anode slurry according to claim 1, in, The mass ratio of the first catalyst to the second catalyst is 1:1-10.

7. The anode slurry according to claim 1, in, When the first catalyst includes iridium element and an alloy of iridium and a non-precious metal, a mass ratio of the iridium element and the alloy of iridium and the non-precious metal is greater than or equal to 1:

1.

8. The anode slurry according to claim 1, in, When the second catalyst includes iridium oxide and oxide of iridium and non-precious metal alloy, the mass ratio of the iridium oxide to the oxide of iridium and non-precious metal alloy is greater than or equal to 1:

1.

9. The anode slurry according to claim 1, in, The mass ratio of the anionic surfactant to the cationic surfactant is 2-5:1, preferably 2-4:

1.

10. The anode slurry according to claim 1, in, The sum of the mass proportions of the anionic surfactant and the cationic surfactant in the anode slurry is 0.03%-0.2%.

11. The anode slurry according to claim 1, in, The anionic surfactant includes one or a combination of two or more of alkylbenzene sulfonic acid surfactants, perfluoroalkyl sulfonic acid surfactants, perfluoroalkyl sulfuric acid surfactants, alkylbenzene sulfuric acid surfactants, perfluoroalkyl carboxylic acid surfactants, alkylbenzene carboxylic acid surfactants, perfluoroalkyl phosphoric acid surfactants, and alkylbenzene phosphoric acid surfactants; Preferably, the anionic surfactant has a carbon number of 12-18.

12. The anode slurry according to claim 1, in, The cationic surfactant includes one or a combination of two or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride, dodecyldimethylbenzylammonium chloride and octadecyltrimethylammonium chloride.

13. The anode slurry according to claim 1, in, The mass proportion of the iridium-based catalyst in the anode slurry is 1%-4%.

14. The anode slurry according to claim 1, in, The mass ratio of the resin to the iridium-based catalyst is 1:3-8.

15. A membrane electrode, comprising the PEM water electrolysis anode slurry according to any one of claims 1 to 14 or made of the PEM water electrolysis anode slurry according to any one of claims 1 to 14.